Accelerating the transition from a linear to a circular healthcare sector: ESCH-R: study design and methodology - Jilske Huijben; Erik van Raaij; Albert Wagelmans; Laura Piscicelli; Wei-Shan Shen; Bas van Vliet; Diederik Gommers; Dick Tibboel; Ellen Bakker; Florijn Dekkers; Florijn Dekkers; Redmer van Leeuwen; et al. (Frontiers in Public Health)
Due to the significant environmental impact of healthcare, there is an urgent need to accelerate its circular transition. We provide an overview of the ESCH-R project study design and methodology for accelerating the transition from a linear to a circular healthcare sector through the development and implementation of circular interventions in the Netherlands. Using a transdisciplinary approach, we will apply the 10-R ladder framework for a circular economy to hospitals. Methods are presented to analyze current clinical practices, policies and requirements for sustainable behavioral change, from material flows and operations to policy and regulations. We describe methods for the development of circular interventions, including business models, contract templates, and product redesigns. Finally, our approach to dissemination and education is presented. The described study design and methods can be used by other hospital (settings) to identify environmental hotspots for circular interventions in their own healthcare practice and for the cross-transfer of knowledge and anticipated challenges in implementing circular strategies. Ultimately, the ESCH-R project will deliver innovative, scalable approaches for hospitals to reduce procurement of raw materials, retain value of medical products, and reduce waste streams, CO2 emissions and pollution.